Surgery Management of Rare Hypertrophic Frenum in an Infant - Sheila de Carvalho Stroppa; Juliana Yassue Barbosa da Silva; Maria Cristina Reis Tavares; João Gilberto Duda; Estela Maris Losso (Case Reports in Dentistry)
To report a rare case of a lateral frenum hypertrophy in an infant, this paper describes the case of a girl who came to a first dental appointment when she was 4 months old. A hypertrophic lateral frenum in the upper left canine region was detected. A great depression in the gingival rodet separated the anterior maxillary segment from the posterior one and also decreased the lip mobility in this region. A frenectomy was performed when the patient was 11 months old and the clinical follow-up was done up to the age of 30 months. There was normalization in the vestibular insertion of the lateral frenum, lip mobility, physiological development of the maxilla, and eruption of the upper incisors, canines, and first primary molars. Infants should go to a dental examination precociously in order to detect possible congenital and development alterations.